Edukasi Pengenalan Pentingnya Investasi pada Siswa SMA Dharma Karya Universitas Terbuka - Yandes, Jufri; Nurhayati, Syafiqoh; Juniadi, Dedy; Destiana; Fadillah, Syarif; Jasrial; Aji Fajar Suryo Antoro; Muhtarom; Husna Putri Pertiwi (LPPM UMRI, 2025)
Abstract In the midst of the times, financial literacy has become an essential skill for the younger generation to manage their finances effectively and face future economic challenges. Through a participatory approach, this activity was carried out in the form of interactive seminars, group discussions, and simple simulations on investment. The material presented included an introduction to investment, its types such as stocks, mutual funds, and gold, as well as the long-term benefits of investing. This Community Service (PkM) activity aims to increase the understanding of Dharma Karya Open University (UT) high school students about the importance of investment. The implementation results showed an increase in students' knowledge of the basic concepts of investment, awareness of the importance of financial management, and interest in starting investment early on. Students are also able to recognize the risks and benefits of various investment options introduced. This activity concludes that well-designed investment education can be the first step in building financial literacy among students. As a follow-up step, it is suggested to develop a program that involves the surrounding environment of students and parents to support the creation of good financial habits. Keywords: Investment, Stocks, Financial Literacy, Dharma Karya UT High School